La Justicia Indígena como medio alternativo para solucionar el delito de abigeato en la comunidad La Palma, cantón Guaranda 2021. - Aldaz Punina, Rodolfo Rimael (2023)
The present research work seeks to carry out an analysis of the indigenous justice procedure as an alternative way to solve the crime of cattle cattle rustling in the community of La Palma del Cantón Guaranda in the year 2021; this investigative study will be carried out around the development of application and respect for the existing legal pluralism in the Republic of Ecuador, legally recognized in the Constitution of the Republic of 2008 and which is in force. Plurinationality and therefore interculturality recognized in the Constitution of 2008, is linked to the notion of legal pluralism, which results in the legal recognition of various legal systems according to the nationalities that exist within the territory of the Ecuadorian State. In the different territorial circumscriptions of the country, when the communities are made up mostly of indigenous people, the application of the special administration of indigenous justice is recognized, in which the territorial authorities will have jurisdiction by virtue of the principle of interculturality; that is under the shelter of the Constitution and respecting its supremacy and content. The crime of cattle rustling is constant in indigenous communities, a crime that harms not only socially, but also the economy and well-being of the rural population, since part of the economy is livestock, not in large quantities, but as a means of subsistence for families. However, the cattle rustling does not stop because ordinary justice, given the remoteness of the places, does not comply with the necessary procedures so that those responsible could be punished. 5 The community of La Palma in the Province of Bolívar, Guaranda Canton, is one of the poorest sectors and its livelihood is agriculture and livestock; despite being part of the rural area, indigenous justice is not applied, the ordinary justice is preferred despite the fact that no positive results are obtained from it and despite knowing who commits the crime of cattle rustling, everything remains in impunity; the processes are archived due to lack of procedural momentum, by virtue of the fact that the communities are far from the cities where the offices of the prosecutor's office and the courts are located. This is why it is necessary to respect the constitutional content. The methodologies to be used in this investigative work are qualitative and quantitative, by virtue of the fact that the facts and social phenomena that I will study in this work are measurable and quantifiable; so I will also measure and establish causal relationships between the variables, to explain the study problem and the current social reality. I will apply the dogmatic and interpretative method, because through these methods an answer to the problem treated is offered from what produces the best possible reconstruction allowed by the legal material that is available. Keywords: Rummagery, Indigenous Justice, Legal Pluralism, Conflict Resolution, crime